Analisis Bibliometrik: Tren Penelitian Pembelajaran Berbasis Etno-Project Based Learning (Etno-PjBL) pada Pendidikan Kimia - Dina Dania Navieta; Jaslin Ikhsan (Jurnal Penelitian Pendidikan IPA, 2026)
This study is a bibliometric research aimed at discussing the development of research on Ethno-Project-Based Learning (Ethno-PjBL) in chemistry education from 2017 to 2024. This study utilised the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) approach with data extracted from Google Scholar using the Publish or Perish (PoP) software. A total of 23 relevant articles were analysed using VOSviewer to identify the highest number of publications, authors with the most publications, research trends, and opportunities for further research. The results of the study indicate that interest in Ethno-PjBL research during 2017 to 2024 showed stable but limited growth, as it experienced both increases and decreases. The highest number of publications occurred in 2021 and 2024, with five publications each. The author with the most publications was Sudarmin from Semarang State University with 7 documents. Ethno-PjBL research focused on several themes, such as ethnochemistry, ethno-STEM, creative thinking skills, development, and teaching materials. The visualisation results show that Ethno-PjBL research focuses on the integration of local culture in project-based chemistry learning. Meanwhile, new topics such as "natural products" and "Ethno-STEM approach" have great potential for further research.